The Thai EPOCH Measure of Adolescent Well-being - Nanni, Alexander; Rhein, Douglas (Journal of Mekong Societies, 2023)
The study and promotion of well-being, particularly among adolescents, is well-documented within the western context. The EPOCH measure was adapted from the PERMA model as a tool to measure adolescent well-being. Cross-cultural and linguistically equivalent versions of the EPOCH model are necessary in order to help make a precise evaluation of adolescents’ well-being in diverse cultures. By conducting psychometric research on the Thai version of the EPOCH scale, we aimed to explore the five-factor model among Thai adolescents. To create and validate a Thai version of the EPOCH, the English version of the EPOCH was back-translated and distributed based on a snowball sampling method on social media. 368 respondents completed the Thai EPOCH. The responses were analyzed to assess the internal consistency of each of the subscales—engagement, perseverance, optimism, connectedness, and happiness. The results indicate that the Thai EPOCH has the potential to be a useful tool for assessing the well-being of Thai speakers.